PRINCIPLES OF ECOORIENTED PUBLIC SOCIO-ECONOMIC POLICY FOR MOUNTAIN TERRITORIES OF THE EUROPEAN UNION: DIRECTIONS FOR IMPLEMENTATION IN UKRAINE (Coordinates of Public Administration, 2026)
The purpose of the article is to substantiate the principles of eco-oriented public socio-economic policy for mountain territories in the European Union and to outline the directions for their implementation in Ukraine, taking into account post-war recovery needs, climate-related risks, and the acceleration of legal approximation to the EU acquis in regional, environmental, and sectoral policies. The study applies comparative legal analysis, an institutional-functional approach, and elements of the public policy cycle analysis, which makes it possible to compare the EU’s understanding of mountain territories, the eligibility criteria for support, and the instruments of economic incentives, environmental integration, and multi-level coordination in the cross-border context of the Carpathian macro-region. It is demonstrated that the EU typically treats mountain territories as functional areas with permanent natural constraints and relies on procedurally secured mechanisms of programming, monitoring, and evaluation, whereas the Ukrainian model has historically been dominated by a settlement-status approach and a prevalence of social-compensatory instruments. The article argues that implementation should be pursued through modernization of special legislation with a shift towards a “mountain territories” regime, the introduction of indicator-based support architecture, development and investment incentives conditional on environmental requirements, as well as codification of eco-tourism and special regimes for mountain agriculture and forestry linked to river-basin management and natural hazard risk governance. It is concluded that the practical meaning of harmonisation lies in reproducing the EU’s regulatory functions that integrate environmental requirements into development decisions and increase accountability and performance of support programmes.